Contribution to the Cimicidae (Hemiptera: Heteroptera) fauna from Argentina: biology and geographical distribution - Roth, Steffen; Hahn, Steffen; Montani, María Eugenia; Coscarón, María Del Carmen (Zootaxa, 2023)
The bed bug family Cimicidae (Hemiptera: Heteroptera) constitutes a group of specialized haematophagous ectoparasitic insects with about 110 species worldwide and 13 species in the Neotropics. Here we provide biological and faunistic observations for 4 out of the 8 species recorded in Argentina. Propicimex tucmatiani (Wygodzinsky, 1951) was recorded for the first time in the Province of Santa Fe and we provide the first barcode sequence for this species. Acanthocrios furnarii (Cordero & Vogelsang, 1928), a mainly ornithophilic species, has been found in a human apartment in Buenos Aires and was probably attacking humans. Bertilia valdiviana (Philippi, 1865) had been reported in 1950 in the Province of Río Negro, we discuss its potential habitat and host association after visiting the only location where this species had been recorded so far in Argentina. Moreover, we provide some natural history data, i.e. developmental stages, sex ratio and feeding habit of the parrot parasite Cyanolicimex patagonicus Carpintero, Di Iorio, Masello & Turienzo, 2010 from a colony in El Condor (Province of Río Negro).